What Is High Enough? Elevated NT-pro-BNP in Decompensated Paroxysmal Supraventricular Tachycardia - Reeves, Shawn; Womack, Clayton; Lutherer, L. O.; Todd, Christopher; Pinkney, Kerrie; Kasemsri, Thivakorn (Journal of Pediatric Intensive Care, 2018)
Since the late 1980s, elevated atrial natriuretic peptide (ANP) was considered the cause of brisk diuresis in adult patients with paroxysmal supraventricular tachycardia (PSVT). Pro-brain natriuretic peptide (pro-BNP) and related molecules, e.g., N-terminal pro b-type natriuretic peptide (NT-pro-BNP) are known biomarkers of heart failure in adult patients from many causes with probable relevance in children. Perhaps, pro-BNP or related molecules such as NT-pro-BNP are useful in the management of PSVT in infants, thus hastening treatment in children who may otherwise significantly decompensate. Case series of one infant and two neonates presenting with cardiogenic shock and evidence of heart failure are presented. Cardiac monitoring or electrocardiogram (ECG) confirmed the presence of PSVT. Adenosine was administered resulting in successful chemical cardioversion with each case. Significantly elevated NT-pro-BNP levels correlated with heart failure prior to cardioversion. In each case, patients were discharged home with lower NT-pro-BNP levels and maintenance with a β-blocker. Due to documented relationships between elevated pro-BNP level and heart failure in adults, the authors measured the related biomarker NT-pro-BNP in each case, as the relationship could be similar in pediatric PSVT. Based on our experience with children in acute heart failure from other causes, NT-pro-BNP can increase to potentially extreme levels in infants. It appears to correlate with clinical signs of insufficient cardiac output, such as tachycardia, respiratory distress, and moribund appearance. Indeed, in the case series, extremely high NT-pro-BNP values were obtained when the patients appeared moribund from decompensated PSVT. The question arising from these observations is: At what level of elevated NT-pro-BNP, would patients be identified for cardioversion prior to appearance of other signs and symptoms? For each patient within the case series, NT-pro-BNP levels of approximately 20,000 pg/mL were indicative of decompensated heart failure, which was subsequently confirmed by examination of the patient. Further investigation is needed to determine the clinical significance of NT-pro-BNP and related peptides in pediatric patients with PSVT and intermittent PSVT. However, the possibility exists that an increase in NT-pro-BNP and related peptides could be a biomarker for cardiac decompensation after prolonged or intermittent PSVT, thereby shortening the time of diagnosis and intervention, and hence, potentially preventing morbidity, mortality, and extended hospitalization. Additional evidence-based research would help provide biomarker information during PSVT allowing practitioners to more objectively analyze risks.
Keywords: BNP; brain natriuretic peptide; NT-pro-BNP; paroxysmal supraventricular tachycardia; infant(s); neonate(s); cardiogenic shock